Constructing the dependent brain: an analysis of the Brazilian media and of the scientific literature on technology addiction - Amaral, Olavo B.; Junqueira, Lara S. (Revista da Biologia, 2018)
Neuroscience is frequently used as an argument in various debates on mental health, such as the definition of some behaviors as pathological. To understand how this happens in the Brazilian media, we analyzed neuroscientific facts mentioned in articles about a controversial diagnosis: internet and or/video gaming addiction. Of 85 articles located in web searches of seven major press vehicles, 25% made allusions to neuroscience. The analysis of two frequently mentioned facts (the similarity between cerebral alterations observed in drug and technology addictions and the release of dopamine as a mediator of reward and addiction to video games) showed inconsistencies between media claims and the available empirical evidence. However, similar biases were already observable in the scientific literature itself, suggesting that the theory of a “dependent brain” in behavioral and chemical addictions seems to be favored by both journalists and scientists